2016
DOI: 10.3389/fpls.2016.01587
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nitrogen Use Efficiency Genes in Barley: Searching for QTLs Controlling Complex Physiological Traits

Abstract: Over the past half century, the use of nitrogen (N) fertilizers has markedly increased crop yields, but with considerable negative effects on the environment and human health. Consequently, there has been a strong push to reduce the amount of N fertilizer used by maximizing the nitrogen use efficiency (NUE) of crops. One approach would be to use classical genetics to improve the NUE of a crop plant. This involves both conventional breeding and quantitative trait loci (QTL) mapping in combination with marker-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 85 publications
(110 reference statements)
1
38
0
Order By: Relevance
“…Of the enzymes constrained in the metabolic model with experimental data, AlaAT was observed to be one of two main enzymes responsible for the in silico differences in metabolism. Additionally, it has been shown that increasing the activity of the enzyme AlaAT enhanced the productivity of several crops (Good and Beatty, 2011;Han et al, 2016). The direct effect of the leaf chlorogenate content on crop yield is not well documented.…”
Section: Predictive Value Of Physiological Markers For Yield and Its mentioning
confidence: 99%
“…Of the enzymes constrained in the metabolic model with experimental data, AlaAT was observed to be one of two main enzymes responsible for the in silico differences in metabolism. Additionally, it has been shown that increasing the activity of the enzyme AlaAT enhanced the productivity of several crops (Good and Beatty, 2011;Han et al, 2016). The direct effect of the leaf chlorogenate content on crop yield is not well documented.…”
Section: Predictive Value Of Physiological Markers For Yield and Its mentioning
confidence: 99%
“…Some HvNRT2 family members require the partner protein HvNAR2.3 to transport nitrate in barley, but not HvNAR2.1 [37]. Some papers have reported that the HvNRT2.1, HvNRT2.2, and HvNRT2.3 genes belong to the high-affinity nitrate transporter family [43,44]. The oocyte data shows that HvNRT2.5 also belongs to the high-affinity nitrate transporter family ( Figure 9A,B).…”
Section: Plant Uptake Of Nomentioning
confidence: 98%
“…Recent advances in high-throughput sequencing have boosted a significant innovation in functional genomic research. To evaluate whether a gene may be a candidate involved in a specific metabolic process, one strategy is to investigate the patterns of gene expression [48]. Thus, to understand how AspATs respond to N, transcription profiling technology was used to analyze gene expression.…”
Section: Mining Expression Profiles Of Aspats In Tissues Of Differentmentioning
confidence: 99%